Quinazoline based 1, 3, 5‐triazine derivatives as cancer inhibitors by impeding the phosphorylated RET tyrosine kinase pathway: Design, synthesis, docking, and QSAR study. Issue 9 (5th August 2019) - Pathak, Prateek; Naumovich, Vladislav; Grishina, Maria; Shukla, Parjanya Kumar; Verma, Amita; Potemkin, Vladimir
Abstract: The present research focused on designing a quinazoline skeleton, framed via 1, 3, 5‐triazine derivatives (QBT) through field mapping and alignment studies. The QBT derivatives were synthesized via time‐ and cost‐effective protocol. The 3D‐QSAR study, computational physicochemical properties, and ADME calculation of the derivatives were performed to establish the affinity towards the biological system. Molecular docking in the adenosine triphosphate binding site of the RET tyrosine kinase domain (PDB ID: 7IVU) was studied to elucidate vital structural residues necessary for bioactivity. The derivatives were evaluated for anticancer potency against TPC‐1 cells (thyroid cancer), MCF‐7 cells (breast cancer), and one normal cell line (human foreskin fibroblasts) via 3‐(4, 5‐dimethylthiazol‐2‐y1)‐2, 5‐diphenyltetrazolium bromide assay followed by an in ovo CAM assay. The entire series of derivatives (8a–o ) showed mild to significant anticancer potency against the selected cancer cell lines. Abstract : A quinazoline skeleton was designed, framed via 1, 3, 5‐triazine derivatives (QBT) through field mapping and alignment studies. The QBT derivatives were evaluated for anticancer potency against TPC‐1 and MCF‐7 cells. Molecular docking in the adenosine triphosphate binding site of the RET tyrosine kinase domain was studied to elucidate vital structural residues necessary for bioactivity.